Simultaneous Heat and Mass Transfer in Kek Lapis Sarawak Baking - Ana Sakura, Zainal Abidin; Nazreen, Junaidi; Andrew Ragai Henry, Rigit; Mohamad Syazwan Zafwan, Mohamad Suffian; Mohamad Syamim, Hamsawi; Shahrol, Mohamaddan; Rasli, Muslimen; Annisa, Jamali (IEEE, 2018)
Kek Lapis Sarawak is a specialty of Sarawak. Nowadays, energy becomes a global issue and there is call to minimize energy consumption for a better tomorrow. In cake industry, the use of oven in baking process contributes to the major energy consumption. This research aims to optimize the baking process for an efficient energy consumption. Therefore, it is very important to investigate the relationship between baking temperature, time and cake quality so that the baking process can be optimized. Kek Lapis Sarawak baking process has been modelled and simulate using finite element method (FEM). Then, results from the model was validated with experiment. As a result, similar model of the Kek Lapis Sarawak baking process has been developed. The finding shows interdependent relationship between porosity, thermal conductivity and moisture content where higher porosity that can lead to poor thermal conductivity.